The Roman food system in Southern Pannonia (Croatia) from the 1st -4th Century A.D. - Reed, K; Roguljić, IO (De Gruyter, 2020)
Food is an excellent medium through which to explore trade, economies, migration and landscapes, yet little is known about food production and consumption in the Roman province of Pannonia. Here we explore the current evidence for agriculture, trade and diet in southern Pannonia (modern day eastern Croatia) and what this may say about life in the region. The influx of new 'exotic' foods and technologies had a profound influence on this region. The limited archaeobotanical data suggests complex trade and local agricultural systems that allowed large towns such as Mursa, Cibalae and Siscia to gain access to a wide range of food items. The large quantities of pottery found not only helps us understand traded goods but also the local tastes and fashions, as well as to infer the types of dishes that could have been cooked. More evidence is clearly needed in this region but what we can see so far is that urban centres along the Danube Limes were firmly integrated within the wider Roman food system and that diets were probably quite varied for many who lived there.